The Integration of Higher Order Thinking Skills in an Indonesian EFL Secondary School English Textbook - Permatasari, Annessia; Muhaji, Uun; Purnawati, Maria (Language Circle: Journal of Language and Literature, 2025)
This qualitative study investigates the extent to which the English for Change textbook for Grade XI integrates Higher Order Thinking Skills (HOTS). Using the Revised Bloom’s Taxonomy as the analytical framework, the study classifies learning activities into six cognitive domains: remembering, understanding, applying, analyzing, evaluating, and creating. Through content analysis, the researchers examined all five units of the textbook, each organized around the four English language skills: listening, speaking, reading, and writing. The findings reveal that although all six cognitive levels are represented in the textbook, the most dominant are remembering and understanding, both of which fall under the category of Lower Order Thinking Skills (LOTS). In contrast, the presence of HOTS levels, analyzing, evaluating, and creating, is noticeably less frequent. Unit 5 features the highest proportion of activities at the creating level. The relatively low integration of HOTS compared to LOTS suggests the need for a more balanced incorporation of higher-order cognitive activities in future textbook designs. This research emphasizes the importance of integrating critical thinking skills across all levels of instruction to cultivate independent, reflective, and creative learners, aligning with the objectives of the latest curriculum.